Supply Chain Infrastructure Development in Russian Economy - Medvedeva, Natalia V.; Frolova, Elena V.; Rogach, Olga V.; Ryabova, Tatyana M.; Sorokina, Larisa N. (International Journal of Supply Chain Management, 2020)
Abstract- The article is devoted to the study of the activities of Zemstvo institutions for the development of supply chain infrastructure in the XIX-early XX centuries; identification of the role of the Zemstvo reform in the formation of supply chain infrastructure at the local level. Supply Chain infrastructure provides the means for chain economic entities and firms sharing a common interest to participate in a mutual exchange. Despite the fact that the provision of supply chain services was not among the priorities of the Zemstvos, significant results were achieved. The retrospective analysis allowed us to highlight the advantages and disadvantages of the Zemstvo self-government system. The comparative method helped to identify trends in the financial and economic support of Zemstvo bodies at various stages of the Zemstvo reform, and to analyze key indicators of supply chain infrastructure development. It is concluded that the success of the Zemstvo self-government bodies in the development of supply chain infrastructure was due to the availability of significant organizational resources, ensuring sustainable interaction of Zemstvos with the population, active support for local initiatives and the formation of a system of public control. The authors note that the experience of implementing the principle of consolidation of the main directions of management activities for the development of supply chain infrastructure, formed by local authorities, can be in demand in modern conditions and adapted to the current system of local government in Russia for economy efficiency.